Solar geoengineering and democracy - Horton, JB; Reynolds, JL; Buck, HJ; Callies, D; Schafer, S; Keith, DW; Rayner, SF (Massachusetts Institute of Technology Press, 2018)
Some scientists suggest that it might be possible to reflect a portion of incoming sunlight back into space to reduce some of the impacts of climate change. Others argue that such solar radiation management (SRM) geoengineering is inherently incompatible with democracy. We draw the following claims from articulations of this argument: (1) that SRM would stretch democratic institutions to the breaking point; (2) that it would preclude opting out, which is essential to democracy; (3) that it would require undue technocracy; and (4) that it would concentrate power and promote authoritarianism. Underlying these claims are two implicit assumptions, that technology has predetermined social effects, and that democracy should be deliberative in orientation. In this article, we reject the argument that SRM is necessarily incompatible with democracy. First, we counter-argue that SRM lacks innate political characteristics, and that democracy need not be deliberative to serve as a standard for governance. We then rebut each of the above claims, countering that democratic institutions are resilient; that opting out is not essential to democracy; that SRM might not require undue technocracy; and that its implementation might not promote authoritarianism. Although we reject the incompatibility argument, we do not argue that SRM is necessarily, or even likely to be, democratic in practice